2018
DOI: 10.13031/jash.12735
|View full text |Cite
|
Sign up to set email alerts
|

Missed Work Due to Occupational Illness among Hispanic Horse Workers

Abstract: Occupational illnesses are inadequately reported for agriculture, an industry dominated by a vulnerable Hispanic population and high fatal and nonfatal injury rates. Work-related illnesses can contribute to missed work, caused by a combination of personal and work factors, with costs to the individual, employer, and society. To better understand agricultural occupational illnesses, 225 Hispanic horse workers were interviewed via community-based convenience sampling. Descriptive statistics, bivariate analyses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Bush and colleagues evaluated the causes of missed work among a sample of Latino horse workers in the USA in an attempt to evaluate the causes of occupational illnesses [65]. The authors found that having at least one child, poor selfrated health, and elevated stress were associated with missed work, highlighting the intersecting role of personal and workrelated factors for these workers.…”
Section: Occupational Injurymentioning
confidence: 99%
“…Bush and colleagues evaluated the causes of missed work among a sample of Latino horse workers in the USA in an attempt to evaluate the causes of occupational illnesses [65]. The authors found that having at least one child, poor selfrated health, and elevated stress were associated with missed work, highlighting the intersecting role of personal and workrelated factors for these workers.…”
Section: Occupational Injurymentioning
confidence: 99%